Development and characterization of edible films based on modified corn starch and grape juice - Yildirim-Yalcin, Meral; Seker, Mahmut; Sadikoglu, Hasan (ELSEVIER SCI LTD, 2019)
Chemically modified corn starch with sodium trimetaphosphate (STMP) or citric acid (CA) and grape juice was used to produce edible films. Modification reactions were discussed by results of FT-IR scan, water solubility, swelling power, viscosity and degree of cross-linking properties. Mechanical, barrier, physical (solubility, color, transparency, microstructure) and glass transition temperature properties of films were studied to understand the effects of grape juice and modified starch usage in films. Usage of starch cross-linked with STMP decreased significantly oxygen permeability from 5.82 to 2.51 cm(3) mu m m(-2) d(-1) kPa(-1), water vapor permeability from 1.89 to 1.38 g mm m(-2) h(-1) kPa(-1), solubility from 0.65 to 0.55 g soluble solid/total solid, percent elongation from 62.96 to 16.47. The chemical reaction between starch and CA affected barrier, solubility and elongation properties of films and values were higher than values of STMP films.
Keywords: Edible film; Grape juice; Water vapor permeability; Oxygen permeability; Cross-linking; Sodium trimetaphosphate; Citric acid; WATER-VAPOR PERMEABILITY; CITRIC-ACID; BARRIER PROPERTIES; MECHANICAL-PROPERTIES; ANTIMICROBIAL PROPERTIES; TENSILE PROPERTIES; POTATO STARCH; WHEAT; Chemistry; Food Science & Technology; Nutrition & Dietetics